HIGHLY RELIABLE I/O MODULE FOR INDUSTRIAL AUTOMATION - TYKHENKO, MAKSYM; BONDARENKO, VIKTOR; BONDARENKO, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article provides an in-depth exploration and practical implementation of the input-output module, designed to meet the heightened demands of industrial automation systems. Distinguished by its robust multi-stage overvoltage protection, the module safeguards discrete inputs against accidental exposure to mains voltage (~220 V), a significant risk in environments prone to unstable power supplies and industrial disturbances. This key feature ensures the safety of equipment and personnel. The introduction underscores the growing importance of resilient and adaptable I/O systems in the context of Industry 4.0, where seamless integration and uninterrupted operation are mission-critical. The paper evaluates several existing solutions – ICP DAS I-7053, Advantech ADAM-4050, and MK110-4DN.4R – emphasizing their limitations in surge protection and diagnostics. This analysis sets the foundation for the proposed innovative approach, combining a powerful STM32F103C8T6 microcontroller, galvanic isolation, RS-485/Modbus RTU communication, and advanced diagnostics via Serial Wire Debug. The hardware employs a tiered protection system with varistors, TVS diodes (SMBJ24A), and relays that disconnect circuits under hazardous conditions. Extensive lab tests validated the module's ability to maintain stable communication, filter input noise effectively, and recover autonomously from fault conditions. LED indicators provide real-time feedback on operational states and emergency events. Future improvements include the adoption of LoRa or Zigbee wireless modules (e.g., E220-900T22D), which will enable cable-free deployment across complex sites, reduce installation costs, and increase the flexibility of the automation system. The proposed input-output module thus presents a comprehensive solution addressing key gaps in the current market, making it highly suitable for critical infrastructure and safety-focused industries.
Keywords: industrial automation; input-output module; surge protection; galvanic isolation; RS-485; Modbus RTU; wireless communication